Ln(x-4)+ln(x-1)=ln(x-8)

Simple and best practice solution for Ln(x-4)+ln(x-1)=ln(x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Ln(x-4)+ln(x-1)=ln(x-8) equation:


Simplifying
Ln(x + -4) + ln(x + -1) = ln(x + -8)

Reorder the terms:
nL(-4 + x) + ln(x + -1) = ln(x + -8)
(-4 * nL + x * nL) + ln(x + -1) = ln(x + -8)
(-4nL + nxL) + ln(x + -1) = ln(x + -8)

Reorder the terms:
-4nL + nxL + ln(-1 + x) = ln(x + -8)
-4nL + nxL + (-1 * ln + x * ln) = ln(x + -8)
-4nL + nxL + (-1ln + lnx) = ln(x + -8)

Reorder the terms:
-1ln + lnx + -4nL + nxL = ln(x + -8)

Reorder the terms:
-1ln + lnx + -4nL + nxL = ln(-8 + x)
-1ln + lnx + -4nL + nxL = (-8 * ln + x * ln)
-1ln + lnx + -4nL + nxL = (-8ln + lnx)

Add '-1lnx' to each side of the equation.
-1ln + lnx + -4nL + -1lnx + nxL = -8ln + lnx + -1lnx

Reorder the terms:
-1ln + lnx + -1lnx + -4nL + nxL = -8ln + lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
-1ln + 0 + -4nL + nxL = -8ln + lnx + -1lnx
-1ln + -4nL + nxL = -8ln + lnx + -1lnx

Combine like terms: lnx + -1lnx = 0
-1ln + -4nL + nxL = -8ln + 0
-1ln + -4nL + nxL = -8ln

Solving
-1ln + -4nL + nxL = -8ln

Solving for variable 'l'.

Move all terms containing l to the left, all other terms to the right.

Add '8ln' to each side of the equation.
-1ln + -4nL + 8ln + nxL = -8ln + 8ln

Reorder the terms:
-1ln + 8ln + -4nL + nxL = -8ln + 8ln

Combine like terms: -1ln + 8ln = 7ln
7ln + -4nL + nxL = -8ln + 8ln

Combine like terms: -8ln + 8ln = 0
7ln + -4nL + nxL = 0

Add '4nL' to each side of the equation.
7ln + -4nL + 4nL + nxL = 0 + 4nL

Combine like terms: -4nL + 4nL = 0
7ln + 0 + nxL = 0 + 4nL
7ln + nxL = 0 + 4nL
Remove the zero:
7ln + nxL = 4nL

Add '-1nxL' to each side of the equation.
7ln + nxL + -1nxL = 4nL + -1nxL

Combine like terms: nxL + -1nxL = 0
7ln + 0 = 4nL + -1nxL
7ln = 4nL + -1nxL

Divide each side by '7n'.
l = 0.5714285714L + -0.1428571429xL

Simplifying
l = 0.5714285714L + -0.1428571429xL

See similar equations:

| lnx=-10 | | 2[x+5(6-x)+18]-10=50-10x | | 28=t+24 | | -8(-8+2p)=192 | | 3x-x+6x=17 | | 12c-4=-12c | | 12-5x=6(x+2) | | 3.4k=7.82 | | 2q-5=11 | | 225x^2-121y^2= | | 7+-3=18 | | 1-100x^2= | | (2c-1)=3c-2 | | 10+5(z-2)=-3z+3 | | 2x^3+3x^2-120=f(x) | | 3/4*3/4= | | -52=5x-4(-x-5) | | 2x^3+3x^2-120=0 | | 10-6x-3=1 | | 24(x+3)=0 | | 28-z=5 | | 2+14a=20a-5a | | z*z-(2+1i)z+(-1+7i)=0 | | -5x+2(-5x-5)=125 | | 2a+14a=20a-5a | | k/9=/18 | | 3-21=3x-9-2x | | -x+70=-86+5x | | 4(3x+2)-18= | | 6(z+2)-(6+4z)=z | | 3(x-3)=4(x+2) | | (4+4)(x+2)=(2+2) |

Equations solver categories